Immune system regulation and response during infectious bursal disease virus and Newcastle disease virus infections in chickens - Pirozyan, Mehdi Rasoli (2013)
Infectious bursal disease (IBD) is caused by IBD virus (IBDV), a highly infectious lymphotropic virus that induces cytocidal effect on B lymphocytes of bursa Fabricius. Hence, the disease has been considered to have the most impact due to its immunosuppressive effects in young birds. However, the effects of the virus on non B lymphocytes functions and secretion of cytokines and chemokines are poorly characterized. On the other hand, Newcastle disease virus (NDV) is a highly infectious virus, which contributed to the major causes of economic losses in poultry industry. The virus can be different into several genotypes, however, velogenic NDV are of genotypes V, VI, VII, VIII and X. Hence, understanding IBDV and NDV immunoregulation on the host immune system will provide valuable information to define the immunopathology of the respective viruses. In this study, immunophenotyping of lymphocytes and productions of cytokines and chemokines expression were analysed by using flow cytometry and GeXP/real-time PCR assays, respectively, in order to understand the roles of B, T cells and macrophages during IBDV and NDV infections. Based on in vitro study, very virulent IBDV strain UPM0081 was detected in monocytes-macrophage cell line, HD11 cells as early as 6 hours post-infection. On the other hand, ConA-C1-Vick, a chicken CD4+ and CD8+ T cell line was not responding against IBDV infection in vitro. In vitro cytocidal effect of IBDV towards HD11 cell line showed evidence of apoptosis where 6% of cells undergo early apoptosis at 24 hours followed by 11% of cells undergo late apoptosis. Up-regulation of pro-inflammatory related cytokines/chemokines and other related genes such as CXCLi1, CXCLi2, CCL4, IL12α, IL-18, IL-1β, iNOS, TLR-3 and MHCI were detected in IBDV infected HD11 cell line. In the in vivo study, vvIBDV (UPM0081) was detected in both spleen and bursa as early as day 2 post-infection in specific-pathogen-free (SPF) chickens based on PCR detection. However, infiltration of Kul1+ macrophages population in spleen and bursa was different. Expressions of cytokines, chemokines and other immunerelated genes in both spleen and bursa were compared in this study to understand the pathogenesis of vvIBDV infection. IL-10, an anti-inflammatory cytokine that commonly expressed by macrophage, was down-regulated in HD11 cells but no significant changes were detected in the bursa and spleen of the infected chicken throughout the study. Unlike constant increase of IL-6, IL-12α, and iNOS in bursa, highest level of IL-6 and IL-12α were found in spleen at day 2 days post-infections while iNOS was recorded with highest expression in spleen at day 3 post-infection. Added to this, IL-8 (CXCLi2) and IL-18 recorded the highest level of expression in day 3 and day 2 post-infection, respectively, in both bursa and spleen. In the case of NDV, immunoregulation of velogenic NDV genotype VII (IBS002) and VIII (AF2240) on chicken macrophages, B and T lymphocytes during the acute stage of the respective virus infection in SPF chickens was characterized. Both NDV genotypes induced drastic reduction of CD4+ and CD8+ T lymphocyte and associated with infiltration of macrophage in spleen at day 3 post-infection. The depletion of the T lymphocytes is probably through the process of apoptosis since 37% and 39% of ConA-C1-Vick cells undergo apoptosis at 24 and 48 hours post-infection, respectively. In addition, gene expression profiles showed an up-regulation of CCL4, CXCLi1, CXCLi2, IFN-γ, IL12α, IL-18, IL-1β, IL-6, iNOS, TLR-7, MHCI, IL-17F and TNFSF13β (p<0.05). However, both genotypes show different expression patterns where IBS002 caused a more rapid up-regulation of CXCLi2, IFN-γ, IL12α, IL-18, IL-1β, iNOS and IL-10 at 3 days post-infection (DPI), meanwhile the expression of CCL4, CXCLi1, IFN-γ, IL-12α, IL-1β and iNOS genes were significantly higher in AF2240 compared to IBS002 at 4 DPI. In addition, the expression of IL-10 was significantly higher in IBS002 infected chickens at 3 and 4 DPI compared to AF2240 infected chickens. Hence, infection with velogenic genotype VII and VIII NDV induce cytokines and chemokines associated with inflammatory reactions. Both the expressions of IFN-γ and CXCLi2 transcripts were up-regulated in CD4+ T cells of AF2240 and IBS002 infected chickens. However, IBS002 showed significantly higher up-regulation of CXCLi2 at day 1 and 3 postinfection compared to AF2240. Furthermore, the up-regulation of IL-18 was readily detectable in IBS002 infected CD4+ T cells at day 1 post-infection. In conclusion, the current study demonstrated the differences in the immunophenotyping of B, T and macrophage populations as well as the expressions of cytokines, chemokines and immune-related genes expression in chickens infected with different genotypes of velogenic NDV strains and vvIBDV. The findings from this study are of valuable information for future study in understanding the immunopathology of the respective virus infection and vaccine –induced immunity.